Dwelling Time pada Sistem dan Prosedur Penanganan Peti Kemas dengan Aplikasi Cost Terminal Operation System di Terminal Peti Kemas Semarang - Riyanto; R.A.J Susilo Hadi Wibowo; Fajar Transelasi; Dewi Kartika Sari (Dinamika Bahari, 2021)
The performance system at the container terminal at Semarang Container Terminal (SCT) is not yet good, it can be seen from the average dwelling time which is still long. Dwelling time optimization needs to be done in order to get a balance of projected increases during trading and to compensate for the various limitations of terminal facilities and infrastructure. One of them is the container handling procedure using an application, namely the cost terminal operating system application. With the qualitative descriptive method, the dwelling time and container handling procedures will be explained using a cost terminal operation system application and the quantitative method is used to find out how much use is in the presence of a vehicle terminal using the formula. There is a very significant positive effect of dwelling time on Port revenue. The long dwelling time is due to several factors, such as high volume / import demand which causes queues during the inspection procedure, 24-hour system inability to perform inspection procedures, weather conditions, and importer readiness. By implementing this system there will be an acceleration of the dwelling time so that Beneficial to importers and the impact caused by container dwelling time after using the cost terminal operation system application is that the waiting time can be reduced.